2016
DOI: 10.1093/nar/gkw1005
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of self-delivering hydrophobically modified siRNA cellular internalization

Abstract: siRNAs are a new class of therapeutic modalities with promising clinical efficacy that requires modification or formulation for delivery to the tissue and cell of interest. Conjugation of siRNAs to lipophilic groups supports efficient cellular uptake by a mechanism that is not well characterized. Here we study the mechanism of internalization of asymmetric, chemically stabilized, cholesterol-modified siRNAs (sd-rxRNAs®) that efficiently enter cells and tissues without the need for formulation. We demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
88
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 81 publications
(98 reference statements)
0
88
0
1
Order By: Relevance
“…These results suggest that (i) the amount of siRNAs required to induce silencing is tissue dependent, (ii) in some tissues a large amount of siRNA is not necessary to induce silencing, and (iii) over a certain amount of siRNAs in the tissue, a portion of the siRNAs is trapped in a nonproductive pathway 45,46 .…”
Section: Lipid-conjugated Sirnas Enable Functional Gene Silencing In mentioning
confidence: 95%
“…These results suggest that (i) the amount of siRNAs required to induce silencing is tissue dependent, (ii) in some tissues a large amount of siRNA is not necessary to induce silencing, and (iii) over a certain amount of siRNAs in the tissue, a portion of the siRNAs is trapped in a nonproductive pathway 45,46 .…”
Section: Lipid-conjugated Sirnas Enable Functional Gene Silencing In mentioning
confidence: 95%
“…To compare two commercially available strategies to conjugate cholesterol to siRNAs (TEG and C7 linkers), we used a previously developed asymmetric siRNA scaffold, 18,40 characterized by a short duplex region (15 bp) and a fully phosphorothioated tail assisting membrane association 18,41,42 (hsiRNAs). hsiRNAs are either partially modified with 2 0 -fluoro pyrimidines on the antisense strand and 2 0 -Omethyl pyrimidines on the sense strand, or they are fully modified using alternating 2 0 -O-methyl and 2 0 -fluoro pattern providing endonuclease stability and protection from innate immune response.…”
Section: Linker Chemistry Influences Efficiency Of Cholesterol-mediatmentioning
confidence: 99%
“…In this protocol, we use self-delivering, hydrophobically modified siRNAs (hsiRNAs) for mRNA silencing. Recent progress in the chemistry of oligonucleotides has enabled the design of these stabilized hsiRNAs, which promote cellular internalization, efficient entry into RISC, and potent knockdown of target genes (Byrne et al , 2013; Alterman et al ., 2015; Ly et al ., 2017). These compounds contain 2’-O-methyl and 2’-fluoro modifications on all sugars and phosphorothioate backbone modifications; the oligonucleotides are often conjugated to a hydrophobic moiety, such as cholesterol, to support membrane binding and cellular internalization without toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the self-delivering properties of hsiRNAs represent an effective method to identify new leads in vitro in complex cellular models, such as primary neurons. We have recently demonstrated that hsiRNAs efficiently bind neuronal-cell membranes within seconds after treatment, enter cells, and induce potent gene silencing, both in vitro , in primary neurons, and in vivo, in mouse brain, all without the use of transfection reagents (Alterman et al ., 2015; Ly et al ., 2017). …”
Section: Introductionmentioning
confidence: 99%